The role of gross mechanical efficiency in endurance sports - Sandbakk, O.; Holmberg, H. C.; Ettema, G. (19th Annual Congress of the European College of Sport Science (ECSS), Amsterdam, 2. - 5. July 2014, 2014)
Gross efficiency (GE) reflects the efficiency of the entire human body in action and provides insight into how the external work rate affects the metabolic cost of the movement. To increase the understanding of the role of GE in endurance sports, our research group has performed a series of experiments investigating the effects of performance level, technique and gender in various sports involving the upper, lower and whole body to various extents. More specifically, work rate and metabolic responses have been measured in ergometer cycling, treadmill roller-skiing with different skiing techniques and terrains and during arm, upper-body and whole body double poling. When comparing different types of locomotion, the magnitude of work rate produced and the way force is generated (i.e., continuous vs discontinuous movement, movement frequency etc.) are the most influential factors affecting GE and not the involvement of the upper and/or lower limbs per se. When correcting for differences in work rate, a higher performance level is associated with better technique and higher GE in technically complex sports. A particular focus has been placed on cross-country skiing where the inter-dependence of power produced by upper and lower extremities leads to large effects of external conditions and technique on GE. In less complex types of locomotion, participants over a large range of fitness levels follow the same work rate-metabolic cost regression lines. Due to differences in physical capacities, men and women at a comparable performance level differ significantly in the technical execution in technically complex movements. However, the two genders show close to identical metabolic costs for a given work rate. In conclusion, work rate, force generation and technique are the major determinants of GE in endurance sports, and men and women demonstrate similar efficiencies.